Entre a prisão do corpo e a liberdade da alma: análise discursiva das correspondências de reeducandos do sistema prisional de Morrinhos- GO - Souza, Ana Cristina (2019)
This research aims at analyzing how inmates of the prison system in Morrinhos-GO see themselves in the conflict zone between prison and freedom that are manifested by the utterances expressed in letters given to extension participants of the Universidade Estadual de Goiás, while they developed a literacy project in the prison system in Morrinhos-GO in 2007 and 2008. Our main questions rely on the possibilities of meanings that their sayings convey, as they express in the letters discourses built by the correctional institutions and internalized by them, which is the opposite of what is expected from the stereotype of a social outcast. Our general purpose is to analyze the stereotype break related to the inmates considering their voices, their discourse positions through spontaneously written letters. It means that when their sayings are considered, they are full of discourse crossings, it is possible to observe in the first place that their voices spread the idea socially built by common sense in a general way, that is, every inmate is an individual without social remedy, which reflects an individual subscribed to familiar, religious discourse, which justifies this research. We sorted the sayings of the inmates, identifying contradictory discourse formations, demonstrating that those individuals has a moving perspective in terms of their opinions about themselves and the world, creating an internal conflict about their conditions: convicted, having the knowledge of that place and with a glimpse of freedom, having discourse memories such as family background, State, religion and other institutional references that constitute social individual. Thus, we aim at understanding how those individuals grasp their situation as inmates and social outcasts and if, indeed, preach civil disobedience or reproduce institutionalized behaviors and, above all, if the discourses match, making the complexity of the inmate that leads to emerging discourses within such a situation. Our theoretical background relies on authors who discuss foucaultians topics, as well as Michel Foucault himself, especially when it comes to discourse formations and the contradictions present in the utterances in the inmates‟ letters; writing about themselves, as a means to be heard and ponder about their condition and relationship of knowledge and power that are typical in the correction environment they are. Also, we will use authors who tackle prison spaces and educational possibilities. Thus, we show a discussion about the inmate and their discourse formations that set them under the idea socially built that inmates will not be rehabilitated, but, if they are given opportunities, guaranteed in law, to restart and resocialize through education, there is a chance that those individuals will resignify themselves for a new social insertion.